New records of longhorn beetles (Coleoptera: Cerambycidae) in Bulgaria - Denis Gradinarov (Silva Balcanica, 2020)
During the period 1969-2019, longhorn beetles (Coleoptera: Cerambycidae) were studied in Bulgaria. In different regions of the country, 144 cerambycid taxa from six subfamilies were established: Prioninae (five species), Lepturinae (37 species and subspecies), Necydalinae (one species), Spondylidinae (nine species and subspecies), Cerambycinae (46 species and subspecies) and Lamiinae (46 species and subspecies). New localities of 14 rare cerambycid taxa were established (Pedostrangalia revestita, Alocerus moesiacus, Anisarthron barbipes, Icosium tomentosum atticum, Paraclytus sexguttatus, Aegomorphus krueperi, Agapanthia frivaldszkyi, Deroplia genei genei, Dorcadion equestre transsilvanicum, Phytoecia albovittigera, Phytoecia praetextata praetextata, Pogonocherus hispidus, Niphona picticornis and Saperda perforata). New longhorn beetles were also found in the West Balkan Range, the Eastern and Western Rhodopes, Maleshevska Planina Mt. and North-eastern Bulgaria. These new records enlarged the knowledge about the regional distribution of longhorn beetles in Bulgaria.